2018
DOI: 10.3389/fnsyn.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

A Revised View on the Role of Surface AMPAR Mobility in Tuning Synaptic Transmission: Limitations, Tools, and Alternative Views

Abstract: Calcium dynamics in presynaptic terminals regulate the response dynamics of most central excitatory synapses. However, this dogma has been challenged by the hypothesis that mobility of the postsynaptic alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid subtype glutamate receptors (AMPAR) plays a role in tuning fast excitatory synaptic transmission. In this review, we reevaluate the factors regulating postsynaptic AMPAR mobility, reassess the modeling parameters, analyze the experimental tools, and end by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(176 reference statements)
1
5
0
Order By: Relevance
“…STED microscopy further showed that these morphological changes occurred both in vitro and in vivo (Hruska et al, 2018; Wegner et al, 2018). The dynamics of SSDs are in agreement with the exchange of individual proteins at synaptic and extra-synaptic sites, which is a hallmark of the dynamic synapse (Choquet and Triller, 2013; Delgado and Selvin, 2018). Therefore, SSDs are momentary representations of the protein distribution and need to be viewed as dynamic snapshots rather than rigid structural units.…”
Section: What Is a Subsynaptic Domain?supporting
confidence: 61%
“…STED microscopy further showed that these morphological changes occurred both in vitro and in vivo (Hruska et al, 2018; Wegner et al, 2018). The dynamics of SSDs are in agreement with the exchange of individual proteins at synaptic and extra-synaptic sites, which is a hallmark of the dynamic synapse (Choquet and Triller, 2013; Delgado and Selvin, 2018). Therefore, SSDs are momentary representations of the protein distribution and need to be viewed as dynamic snapshots rather than rigid structural units.…”
Section: What Is a Subsynaptic Domain?supporting
confidence: 61%
“…However, recovery from MK-801 blockade has not been observed in hippocampal slices (Harris and Pettit 2007), a more physiologically relevant system. In addition, the use of quantum dots to label synaptic single molecules has been called into question because of their size and accessibility to synaptic space (Delgado and Selvin 2018). In this study we used MK-801 blockade of synaptic receptors in organotypic hippocampal slices to study whether NMDARs are able to diffuse in the plane of the membrane entering and leaving synaptic areas.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that extrasynaptic and synaptic NMDARs form stable pools (Harris and Pettit 2007). In addition, questions regarding whether quantum dots used for single-molecule tracking can reliably access the synaptic space makes previous observations of rapid lateral diffusion of synaptic receptors using this method of tracking unclear (Delgado and Selvin 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2A-B, D). However, high concentration of SA (50 nM of free SA or 500 nM of SA-dye conjugates) has been shown to crosslink surface AMPARs and other proteins ( 12, 22 ); therefore, we used much lower concentration of SA-Atto647N (0.6 nM) (Fig. 2, 3), which we have previously verified not to induce cross-linking of AMPARs ( 4 ).…”
Section: Resultsmentioning
confidence: 99%